9 - The Stars Must Shine: Nollywood Talent Scouts’ Influence on Theatre Arts Students’ Body Image in Nigerian Universities - Ikuomola, Adediran Daniel (Africa Development, 2018)
The influence of the Nigerian film industry, (Nollywood) on youth culture is overwhelming with several talent hunt shows organised to recruit them young at schools, with the promise of making them superstars. This has also impacted on the rate at which students seek admission into universities to study theatre art. This article examines Nollywood talent scouts’ influence on theatre arts students’ body image as well as talent in selected Nigerian universities. Specifically, the study investigates scouts’ intrigues on the dynamics of cosmetic usage, bodily and behavioural adjustments of male and female students. The study shows that theatre art students’ first time contact with Nollywood scouts and talent hunters marks the beginning of their celebrity consciousness and sojourn in the world of bodily enhancements. Students’ narratives shows that scouts and talent hunters’ concerns were initially on their bodily appearance, height, complexion and weight before their talents and abilities. Thus, at the end, different shades of lighter skin, side beards, and bodily uplifts emerged with different attributions corroborating scouts’ narratives. The article concludes that the influence of Nollywood scouts, through talent hunts, creates a diversionary atmosphere for learning, with expensive and vulnerable lifestyles on and off campus.